Trash to treasure: Leaf-cutting ants repair nest-mound damage by recycling refuse dump materials - Farji Brener, Alejandro Gustavo (2012)
Animals adjust their behaviors in response to changing environmental conditions because the costs and benefits of such behaviors change as conditions change. The reuse of materials from waste (i.e., recycling) rarely occurs in social insects because it may imply significant health risks and behavioral difficulties. However, the benefit of reusing may exceed its costs under certain circumstances. For the first time, we document that ants "recycle" refuse materials to repair nest-mound damage. We conducted a series of field measurements and experiments to test the hypotheses that fluctuations in this behavior in the leaf-cutting ant Acromyrmex lobicornis depend on 1) seasonal changes in the tendency to reject refuse (a proxy of changes in their pathogen levels), and/or 2) seasonal foraging restrictions. We 1) measured the rejection of foraging ants toward experimental refuse piles among seasons and 2) analyzed how mound condition, temperatures of fungus chamber and soil surface, and foraging activity explained this behavior using a classification tree, a powerful recursive partitioning method. Foraging ants showed similar rejection levels toward refuse piles in different seasons. Colonies repaired mound damage with refuse materials only during the hottest season and when they had low foraging rates, suggesting that ants recycle their refuse by a hierarchical set of decisions dependent on the risk of fungal damage and foraging restrictions. Repairing the mounds is essential during summer, when temperatures inside damaged mounds are lethal to their fungus cultures. However, these high temperatures also restrict the foraging activity, reducing the collection of building materials. Thus, colonies with lower foraging rates apparently use their refuse to repair mounds because this substrate requires less searching and carrying time. The use of refuse did not affect the colony growth rate. This illustrates how ants integrate information about food, hygienic and nest conditions through a novel and plastic behavior: recycling of their discarded materials.